Village Development Activities in the Women's Empowerment Program through Writing Batik in Creating an Economic Creative Village (Study in the Abolition Village of Dukuhturi District, Tegal Regency - Ramadhani, Pawitrasari Mahestyas (2020, 2020)
Village Development Activities in the Women's Empowerment Program through Writing Batik in Creating an Economic Creative Village (Study in the Abolition Village of Dukuhturi District, Tegal Regency): This service aims to provide an overview of the preparation, implementation, results of the program and the impact of the women's empowerment program in the Tegal Dukuhturi Sub-District. This dedication is a qualitative research. The subject of this devotion is the head of the group and housewives who are members of the Customs written batik group. Data collection techniques are done through interviews, observation and documentation. In collecting data, researchers are assisted by observation guidelines, interview guidelines and documentation guidelines. Data analysis was performed by data reduction, data presentation and conclusion drawing. The results of the study reveal: (1) Preparation of batik skills programs is carried out through program socialization to housewives through social gathering and PKK meetings, group member registration and determination of the time and place for batik implementation. (2) Making batik is carried out from 08.00 - 15.30 WIB. The work system is carried out in groups where each group has a duty to make batik using the facilities provided. (3) The results of this women's empowerment program include housewives having batik skills activities, and educating to be independent. (4) The impact of implementation includes improving social status, increasing family economic income. . Keywords— Pengababean Village, written batik group, Empowering women